Clandestine Migration and the Politics of Form in Nicole Caligaris’s Les Samothraces - Oana Sabo (Studies in 20th & 21st Century Literature, 2018)
This article analyzes Nicole Caligaris’s Les Samothraces (2016), an experimental literary text about undocumented migration, in light of Theodor Adorno’s aesthetic reflection on the politics of literary form and Thomas Nail’s political theory of the migrant. Reading Les Samothraces against the grain, I argue that the text’s literary form encodes the political tensions of its contemporary moment, namely the tension between the free movement of migrants and Europe’s policing of its borders. Analysis of formal elements—literary characters, plot structure, and inclusion of photographs—that depict migrants who escape capture by regimes of surveillance shows that the text is an apology for migration and a critique of border politics.
Keywords: contemporary French literature; clandestine migration; the figure of the migrant; the politics of form